Experiences of Time and Timelessness in Electroacoustic Music - Noble, Jason; Bonin, Tanor; McAdams, Stephen (Organised sound : an international journal of music technology, 2020)
Electroacoustic music and its historical antecedents open up new ways of thinking about musical time. Whereas music performed by humans is necessarily constrained by certain temporal limits that define human information processing and embodiment, machines are capable of producing sound with scales and structures of time that reach potentially very far outside of these human limitations. But even musics produced with superhuman means are still subject to human constraints in music perception and cognition. Focusing on five principles of auditory perception – segmentation, grouping, pulse, metre and repetition – we hypothesise that musics that exceed or subvert the thresholds that define ‘human time’ are likely to be recognised by listeners as expressing timelessness. To support this hypothesis, we report an experiment in which a listening panel reviewed excerpts of electroacoustic music selected for their temporally subversive or excessive properties, and rated them (1) for the pace of time they express (normative, speeding up, or slowing down), and (2) for whether or not the music expresses ‘timelessness’. We find that while the specific musical parameters associated with temporal phenomenology vary from one musical context to the next, a general trend obtains across musical contexts through the excess or subversion of a particular perceptual constraint by a given musical parameter on the one hand, and the subjective experiences of time and timelessness on the other.